What Is Successful Aging? A Psychometric Validation Study of Different Construct Definitions. (17th July 2018) - Kleineidam, Luca; Thoma, Myriam V; Maercker, Andreas; Bickel, Horst; Mösch, Edelgard; Hajek, André; König, Hans-Helmut; Eisele, Marion; Mallon, Tina; Luck, Tobias; Röhr, Susanne; Weyerer, Siegfried; et al.
Abstract: Background and Objectives: We examined the validity of 5 successful aging (SA) operationalizations that assessed different facets of the SA construct (cognitive and physical health and disability; well-being; social engagement). Research Design and Methods: A total of 2, 478 participants (mean age = 82.5 years, standard deviation [ SD ] = 3.47) were studied. We used confirmatory factor analysis to investigate the relationships between facets and to determine the convergent validity as well as short-term (1.5 years) and long-term (4.5 years) predictive validity of the 5 SA operationalizations for measures of quality of life (QoL) and objective health outcomes. Results: A general SA operationalization that included all SA facets but also allowed differences between them showed the best model fit and construct validity. A biomedical operationalization of SA that excluded either the well-being or the social engagement facet showed lower convergent and predictive validity for subjective measures (e.g., QoL) but higher associations with objective measures (e.g., health). A purely psychosocial SA operationalization that excluded the physiological facet did not allow good prediction of objective health outcomes. Discussion and Implications: Our results suggest that a well-balanced SA operationalization should include measures assessing health, disability, well-being, and social engagement.